MORPHOLOGICAL AND PHYSICOCHEMICAL CHARACTERISATION OF DATE PALM CULTIVARS FROM GHARDAÏA (SOUTHEAST ALGERIA) - Abdelkader ALLAM; Kaouthar DJAFRI; Meriem BERGOUIA; El-Haîfa KHEMISSAT; Mohamed TAMA; Brahim TALEB (Journal of Applied Life Sciences and Environment)
The date palm (Phoenix dactylifera L.) is an economically important species vital for food security in Algeria, especially for the southern population. There are an estimated 18 million palm trees in Algeria with more than 1000 cultivars. This poorly known resource is unfortunately threatened with extinction. This work was carried out on 24 date palm cultivars, studying their morphological and physicochemical characteristics, such as the weight, length and diameter of the date and the seed, and the consistency, moisture, pH and sugar content of the dates. Ten homogeneous palm trees were selected for each cultivar. From each tree, we collected 40 fruits devoid of their calices (4-5 fruits per bunch), at different heights and orientations in each bunch. The results show that the morphological and physicochemical characteristics vary from one cultivar to another. The dates of most cultivars have a combination of good and bad characteristics. The cultivar Tmar-Bousbaa has very high values for the characteristics weight, length, and diameter of the date and seed (23.16 g, 4.90 cm, 2.85 cm, and 1.53 g, 2.74 cm, 0.94 cm, respectively). The cultivars Takarnait and Halwa have high acidity, varying between 1.08 and 1.92 g/kg of fresh material and a pH of less than 5.46. The cultivar Bouarous has a low sugar content: less than 63%. Principal component analysis (PCA) was used to analyze the whole dataset, revealing high variability among the cultivars. Thus, out of 14 characteristics investigated, ten have been shown to be strong discriminating factors.